Investigating the effects of personal entrepreneurial characteristics - Masoumeh Sadat Abtahi; Mohammadreza Karamipour; Kobra Abbasi (Management Science Letters)
This paper presents an empirical investigation to study the impacts of personal entrepreneurial characteristics including “Need to succeed”, “Idea fluency” and “Pragmatism” among students who were enrolled in different fields at Islamic Azad University of Zanjan, Iran. Using a standard questionnaire, which is modified for Iranian culture, the study measures the effects of three factors. The results of Kolmogorov-Smirnov indicate that all three variables of the survey were normally distributed. The results of t-student test for “Need to succeed” is equal to 28.623 with df = 349 and Sig. = 0.000, which is statistically significant. In addition, t-student test for “Idea fluency” is equal to 16.124 with df = 349 and Sig. = 0.000, which is also statistically significant. Finally, the results of t-student test for “Pragmatism” is equal to 31.255 with df = 349 and Sig. = 0.000, which is statistically significant. The findings indicate that the participants hold relatively high level of personal entrepreneurial characteristics.